Acessibilidade e mobilidade dos pedestres frequentadores e moradores próximos aos parques Areião e Vaca Brava em Goiânia-GO. - Cunha, Esther Milhomem de Oliveira (2015)
The population growth and socioeconomic development of cities are followed by the deterioration of quality of life of residents that is invariably related to their capacity of moving around in their daily routine. In recent decades, the city of Goiania showed a high growth rate resulting in urban issues that interfered regarding accessibility and mobility of pedestrians. In this sense, the present study aimed to analyses the situation of accessibility and mobility of pedestrians living in the neighbourhoods of Areiao park and Vaca Brava park, that are seen as upscale areas, it pointed out the level of service of the sidewalks around the parks, and more specifically, it verified the differences of the indicators of accessibility and mobility in the surroundings of the two parks. Therefore, an analysis of physical environment in the surroundings of streams Areiao and Vaca Brava was performed, through the elaboration of thematic maps as slopes, hypsometry, long strands and altimetric diversity; the methodological approach of Ferreira and Sanchez (1998) was used, applied in 80 points distributed in the two basins; 240 questionnaires were applied, 120 in each basin. The analysis of the physical environment identified that the basins of Areiao and Vaca Brava streams have factors that increase the acceleration of the surface runoff, fostering the erosion of the streets and sidewalks of the areas adjacent to parks, as well as floods. Taking use of Ferreira and Sanchez methodology (1998) it was possible to indicate that the level of service is predominantly between good to regular, varying between 55% and 80%; and bad to very bad, between 45% and 15%, respectively for the Areiao Park and Vaca Brava Park. The region of Vaca Brava Park presented higher level of service regarding accessibility and mobility than Areiao Park region. The interviews carried out confirmed the results obtained by the methodology of Ferreira and Sanches (1998) and pointed out that the quality of the sidewalks is between regular and bad. The characteristics of the physical environment are factors that can increase the process of erosion and flooding of streets and sidewalks, but these factors isolated do not justify the precarious conditions observed on the sidewalks of the two areas surveyed. The environmental interference could be easily reduced with appropriated adaptations, maintenance and quality control by the government, following the laws related to urban mobility and accessibility. Walking on the streets of an upscale neighbourhood of Goiania, still not representing quality of life for the population.